PERANCANGAN ILLUSTRATION HANDBOOK MOJOKERTO SERVICE CITY SEBAGAI UPAYA MEMPROMOSIKAN KOTA MOJOKERTO - Sjam, Shofi Sabian; Budiardjo, Hardman; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
AbstractMojokerto as a buffer city of Surabaya is expected to become a service city (city service) which has advantages including Manusi Resources (HR). In addition to want to be known as mojokerto service city, Mojokerto also make city service program has been implemented by the Government of Mojokerto since 2014, the program is expected to be the flagship program of Mojokerto in the field of care and services. But many people outside the city and residents of the town of Mojokerto Mojokerto not understand this program. In addition, it is also expected that people outside the town of Mojokerto also know that the city or town serve excellent service is Mojokerto. Departing from these problems purpose of this research to design handbook illustration Mojokerto service city in an effort to promote the city of Mojokerto.Â Keyword: illustration, handbook, Mojokerto service city